Redirecting abiraterone metabolism to fine tune prostate cancer anti-androgen therapy - Li, Zhenfei (Nature, 2016)
Abiraterone blocks androgen synthesis and prolongs survival in castration-resistant prostate cancer, which is otherwise driven by intratumoral androgen synthesis(1,2). Abiraterone is metabolized in patients to D4A, which has even greater anti-tumor activity and structural similarities to endogenous steroidal 5α-reductase substrates, such as testosterone(3). Here, we show that D4A is converted to at least 3 5α-reduced and 3 5β-reduced metabolites. The initial 5α-reduced metabolite, 3-keto-5α-abi, is more abundant than D4A in patients with prostate cancer taking abiraterone, and is an androgen receptor (AR) agonist, which promotes prostate cancer progression. In a clinical trial of abiraterone alone, followed by abiraterone plus dutasteride (a 5α-reductase inhibitor), 3-keto-5α-abi and downstream metabolites are depleted, while D4A concentrations rise, effectively blocking production of a tumor-promoting metabolite and permitting D4A accumulation. Furthermore, dutasteride does not deplete three 5β-reduced metabolites, which were also clinically detectable, demonstrating the specific biochemical effects of pharmacologic 5α-reductase inhibition on abiraterone metabolism. Our findings suggest a previously unappreciated and biochemically specific method of clinically fine-tuning abiraterone metabolism to optimize therapy.